Needs analysis of expository writing teaching materials based on Toulmin's argumentation patterns - Boeriswati, Endry; Eriyani, Reni Nur; Wibawani, Sri (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to analyze the needs of teaching materials for writing exposition based on Toulmin's argumentation pattern. Through observations, interviews, and document studies, it was found that students' argumentation skills still tend to be low. The existing teaching materials are considered inadequate in providing clear and systematic guidance to build strong arguments. The results of the analysis show that students predominantly use basic argumentation patterns and have difficulty in developing complex argumentation. This can also be seen from the learning outcomes of students who are at an average score of 61.37 in the poor category. This illustrates that most learners still need significant improvement in writing expositions. Then, the standard deviation of 12.854 shows the diversity of learners' abilities in writing expositions. This is in line with the results of interviews with teachers that students' abilities in writing expositions vary; most are still in the basic stage, but there are also students who show good potential, although they still need further guidance. Therefore, the development of teaching materials that integrate Toulmin's argumentation pattern is considered very relevant to improve students' exposition writing skills.